IgG4-related disease; a unifying entity - Mohammadreza Ardalan; Kasra Ardalan (Society of Diabetic Nephropathy Prevention, 2018)
IgG4-related disease (IgG4-RD) is characterized by dense lymphoplasmacytic infiltration of different organs and elevated serum IgG4 level. The disease involves different organs including pancreas, kidney, aorta, lung, thyroid, salivary and lacrimal glands. IgG4-RD mimics malignancies, infectious and inflammatory disorders. Many disorders previously regarded as isolated, single-organ diseases such as autoimmune pancreatitis type 1, Mikulicz disease, and Riedel thyroiditis are connected within the spectrum of IgG4-RD. Chronic interstitial nephritis (CIN) is the main type of renal involvement. Membranous nephropathy is another renal picture of IgG4-RD. Multiple, hypo-dense, cortical, round and wedge-shape lesions are the main renal ultrasound features. IgG4-RD during its inflammatory phase successfully responds to glucocorticoid therapy. Here we presented a case of IgG4-RD and then reviewed the existing literature.